Capturing dynamics in business model frameworks - Hanieh Khodaei; Roland Ortt (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Business model dynamics is important, because high-tech companies, the technology that they commercialize, and the market in which they operate all change over time. We build on the dynamic capability view of the firm to explain business model evolution and innovation, looking particularly at the dynamics that are created by interactions between business model components over time. We use the following four criteria to assess the degree of dynamics in business model frameworks: completeness of business model aspects, interrelationships between aspects, interrelationships over time, and framework changes over time and across contexts. Business model completeness involves internal company aspects and external environmental aspects. Interrelationships of business model aspects are required to assess business model coherence, which is an important indicator of business model quality. Interrelationships between the environment and business model aspects are required to assess the fit of a particular business model in its context. Interrelationships of these aspects over time are needed to understand business model evolution. Finally, business model frameworks need to be adapted over time and across contexts to keep frameworks simple and useful yet complete. Our analysis shows that current business model frameworks do not meet all four criteria, and thus only partly incorporate dynamics.
Keywords: 650; business model canvas; business models; dynamics; criteria; dynamic capabilities